ANALISIS KETERAMPILAN KEAKSARAAN AWAL ANAK KELOMPOK A PADA PEMBELAJARAN BAHASA INGGRIS DI TK AL-AZHAR 35 SURABAYA - Aninda Tusyifa Faridatu Rohmah; Sri Setyowati; Mallevi Agustin Ningrum; Yes Matheos Lasarus Malaikosa (Alzam: Journal of Islamic Early Childhood Education, 2026)
Early reading skills are a crucial literacy foundation for young children, yet they are often taught using monotonous conventional methods. This study aims to analyze the implementation of English language learning in stimulating early reading skills in Group A children (aged 4-5 years) at TK Islam Al-Azhar 35 Surabaya. This study employed a descriptive qualitative approach with a case study design. Data were collected through non-participant observation, in-depth interviews with teachers and the school principal, and documentation. The data analysis technique followed the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results indicated that the stimulation of early reading skills was implemented integratively through the "English Super Safari" program and the involvement of Native Speakers using the Total Physical Response (TPR) method and multimodal media. The findings revealed that the children demonstrated significant progress in recognizing the English alphabet, phonetic awareness, and the ability to read simple pictures and words within a literacy-rich environment. The conclusion of this study confirms that introducing a foreign language through interactive and activity-based methods is not a cognitive burden for children; rather, it serves as an effective stimulant that strengthens their early literacy readiness and metalinguistic awareness.